Drying temperature effects in peppermint essential oil content and composition - Blanco, M. C S G (2002)
Studies were conducted to show the effect of different temperatures in the drying process on the amount and quality of essential oils of peppermint (Mentha piperita L.) The leaves were harvested in the Demeter Farmer, Botucatu, SP, Brazil in december, 1997. The leaves were dried at 40°C, 60°C and 80°C, until establishment of the weights. The essential oil was extracted by destilation in Clevenger apparatus and analysed by GC-MS. Higher drying temperature sharply decreased the essential oil content (% v/w) from 1.0% (40°C) to 0.14% (60°C) and 0.12% (80°C). Higher drying temperatures also affected the composition, decreasing the contents of 1,8 cineol and citronelal until 80°C, and increasing the contents of menthol and neomenthol until 60°C.